Reductive cleavage of P-4 by iron(I) centres: synthesis and structural characterisation of Fe-2(P-2)(2) complexes with two bridging P-2(2-) ligands - Yao, Shenglai; Szilvasi, Tibor; Lindenmaier, Nils; Xiong, Yun; Inoue, Shigeyoshi; Adelhardt, Mario; Sutter, Jörg; Meyer, Karsten; Driess, Matthias (Chemical Communications, 2015)
The selective transformation of white phosphorus with a beta-diketiminato iron(I) toluene complex under mild reaction conditions is reported which furnishes a new dinuclear iron(III) Fe-2(P-2)(2) complex with two bridging P-2(2-) ligands. Its reduction with potassium results in the formation of the first delocalised mixed-valent bis-diphosphido iron(II,III) complex which is isostructural with the neutral Fe2P4 precursor.